2017
DOI: 10.1155/2017/8976754
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinvasive Infection from O117:K52:H-Escherichia colifollowing Acute Pyelonephritis

Abstract: Spontaneous or nosocomial Escherichia coli meningitis remains rare in healthy adults but is still carrying a high mortality rate despite adapted antimicrobial treatment for susceptible strains. A 39-year-old woman was admitted to the hospital with severe subarachnoid haemorrhage complicated by acute hydrocephalus. On hospital day 10, she developed Streptococcus anginosus septicaemia and urinary tract infection due to a multisensitive strain of E. coli. This infection was successfully controlled by antimicrobia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Cromlin et al reported a case of O117:K52: H E. coli meningitis and multiple brain abscesses with the demonstration of acute pyelonephritis as the primary source. The patient died from complications [9]. Common risk factors for GNB meningitis include cirrhosis, alcoholism, malignancy, diabetes mellitus, immunosuppressive drugs and HIV infection [10].…”
Section: Discussionmentioning
confidence: 99%
“…Cromlin et al reported a case of O117:K52: H E. coli meningitis and multiple brain abscesses with the demonstration of acute pyelonephritis as the primary source. The patient died from complications [9]. Common risk factors for GNB meningitis include cirrhosis, alcoholism, malignancy, diabetes mellitus, immunosuppressive drugs and HIV infection [10].…”
Section: Discussionmentioning
confidence: 99%